Technology in Hospital Supply Chain Management - Marla Setiawati; Evelyn Arnetta Rahayu; Zefania Abigail (IPTEK The Journal for Technology and Science, 2026)
The healthcare industry is currently advancing, so it is necessary to integrate the technology used by hospitals. Hospital technology integrates data collection, data management, and information presentation. In fact, in the current hospital supply chain technology, it has not been integrated so it requires further research. This research discusses hospital supply chain technology that uses several technologies, namely blockchain, Internet of Things (IoT), Radio Frequency Identification (RFID), Artificial Intelligence (AI), telemedicine, and Hospital Information System (HIS). The technology used needs to be integrated so that it can help the entire system in the hospital properly. In the technology used, there are several variables that affect technology integration so that it needs to be considered, such as the level of integration, level of accuracy, data security, trust between stakeholders, information quality, system quality, efficiency level, perceived ease of use, perceived usefulness, reliability level, and real time. Then proceed to use the Causal Loop Diagram to visualize the relationship between variables that affect the level of integration between technologies. With integrated technology, the hospital supply chain process will become more efficient and also increase trust between stakeholders in the hospital in using the technology. This study highlights the limitations of the research and suggests areas for future research, such as using the SFD (Stock Flow Diagram) method to further investigate the supply chain technologies used by hospitals.